Influences of pretreatment, extraction variables, and post treatment on bench‐scale rice husk black ash (RHBA) processing to bio‐silica. Issue 5 (8th August 2021) - Steven, Soen; Restiawaty, Elvi; Pasymi, Pasymi; Bindar, Yazid
Abstract: Abundant availability and large silica content in rice husk black ash (RHBA) make the use of it very interesting to study. Many works only deal with lab‐scale rice husk ash extraction while the studies on bench‐scale RHBA extraction are still limited. This study, hence, presents the influence of pretreatment, extraction variables, and posttreatment on bench‐scale RHBA processing to bio‐silica. The pretreatment through acid leaching was carried out using HCl. The extraction was implemented under varying process variables such as alkaline‐to‐feed ratio (RA/F ), extraction duration, and acid precipitation agent. According to this study, the highest extraction yield up to 98% was gained under RA/F 6 g/g and 1‐h extraction. The amorphous bio‐silica had an asymmetric siloxane bond and white appearance with a purity exceeding 95% and surface area up to 406.98 m 2 /g. Meanwhile, precipitation under HCl and H2 SO4 had little impact on product purity and surface area. This study exhibits that acid leaching is executed to release mineral impurities but is still not sufficient to remove the remaining carbon content in bio‐silica. However, the contribution of refining process is able to do so. Moreover, the produced bio‐silica is suitable for adsorbent purposes which could adsorb up to 83.5% of 3‐monochloropropanediol compound.